Lexicon on Board: A MEG Study Based on Expressive Picture-Naming - Tabari, Fatemeh (East European Journal of Psycholinguistics, 2021)
No task can better depict the path underlying word production in human brain than picture naming as it covers all the stages of production from visual analysis to motor execution. Nevertheless, the cognitive processes associated with word retrieval and the investigation on word-picture differences are complex and not fully understood. Uttering a word entails orchestrating several steps as visual object recognition, accessing a lexical concept, lemma selection, lemma retrieval, accessing the morpheme(s) and generating the phonological word, and finally retrieving syllabic gestural scores and articulation. Moreover, it is already known that the brain function is not the outcome of isolated regions but the network of regions interacting with each other. To study the mechanisms of word retrieval in lemma selection phase, we compared the three groups of monolingual, semi-bilingual and bilingual learners Spanish-English speakers through a functional neuroimaging technique with respect to their topography and strength of Functional Connectivity (FC) values of the most highlighted pair of activated nodes in the time range of 0-150 ms in different frequency bands (delta, theta, alpha, beta, and. gamma) upon application of the stimuli. We have seen no significant difference between difference frequency bands (p > .05) at the most highlighted FC pairs. However, we observed higher gamma values signifying the semantic activation of the word. We could not find any significant difference between the three groups in terms of FC values at designated pairs of nodes signifying that different amount of exposure could not affect electrophysiological patterns in the preliminary step of word production.Acknowledgements This study was supported by the Portuguese Foundation for Science and Technology and the Portuguese Ministry of Science, Technology and Higher Education (UID/PSI/01662/2019), through the national funds (PIDDAC).